Peran Karyawan Dinas Kebudayaan Dan Pariwisata Dalam Pengembangan Sumber Daya Manusia Di Era-Digital Pada Pokdarwis Pantai Tlangoh Bangkalan - Syaiful Amin; RM. Moch. Wispandono (Journal Of Business, Finance, and Economics (JBFE), 2023)
Tourism in Bangkalan Regency has great potential, especially in Tlangoh Beach. In the development of the digital era, the role of employees of the Culture and Tourism Office is becoming increasingly important in advancing human resources in the Tlangoh Beach Tourism Awareness Group (Pokdarwis). This research aims to explore and analyze the role of employees of the Culture and Tourism Office in developing human resources in the digital era. The Tourism Office plays a very significant role in managing the human resource development efforts at Tlangoh Beach. They act as facilitators in training and skills development for the Tourism Awareness Group (Pokdarwis), as well as connecting them with adequate human resources in responding to changes in the digital era. This research employed a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. However, challenges faced by Tourism Office employees were also identified, including a deeper understanding of digital technology, more effective coordination with relevant stakeholders, and adaptation to rapid changes in the tourism industry. This research is expected to provide a clearer view of the role of Tourism Office employees in human resource development in the digital era, as well as provide contributions to policymakers to increase tourism potential at Tlangoh Beach, Bangkalan Regency.